Circular RNA expression profiles and functional predication after restraint stress in the amygdala of rats - Wang, Chuan; Wang, Qian; Xu, Guangming; Sun, Zhaoling; Zhang, Dong; Ma, Chunling; Li, Yingmin; Wen, Di; Zhang, Xiaojing; Cong, Bin (Frontiers in Molecular Neuroscience, 2024)
Prolonged or repeated exposure to stress elevates the risk of various psychological diseases, many of which are characterized by central nervous system dysfunction. Recent studies have demonstrated that circular RNAs (circRNAs) are highly abundant in the mammalian brain. Although their precise expression and function remain unknown, they have been hypothesized to regulate transcriptional and post-transcriptional gene expression. In this investigation, we comprehensively analyzed whether restraint stress for 2 days altered the circRNA expression profile in the amygdala of male rats. The impact of restraint stress on behavior was evaluated using an elevated plus maze and open field test. Serum corticosterone levels were measured using an enzyme-linked immunosorbent assay. A total of 10,670 circRNAs were identified using RNA sequencing. Ten circRNAs were validated by reverse transcription and quantitative polymerase chain reaction analysis. Gene ontology and Kyoto encyclopedia of genes and genomes pathway analyzes supported the notion that genes associated with differentially expressed circRNAs are primarily implicated in neuronal activity and neurotransmitter transport. Moreover, the three differentially expressed circRNAs showed high specificity in the amygdala. Overall, these findings indicate that differentially expressed circRNAs are highly enriched in the amygdala and offer a potential direction for further research on restraint stress.